2002
DOI: 10.1002/sia.1421
|View full text |Cite
|
Sign up to set email alerts
|

Reflectometry studies of the oxidation kinetics of thin copper films

Abstract: Oxide formation on magnetron-sputtered thin copper films (35 nm thickness) was studied by x-ray reflectometry and grazing incidence x-ray diffraction. The films were oxidized in air at temperatures of 175•

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(10 citation statements)
references
References 7 publications
0
10
0
Order By: Relevance
“…growth of thickness of the oxide as a function of time, and they are summarised in Fig 11. A number of theories have been proposed [277][278][279][280] , mostly based on the Cabrera and Mott 281 theory and they postulate that, under the assumption of uniform epitaxial growth, the thickness of a metal oxide increases following an inverse logarithmic rate law for very thin films (up to 7.3 nm for Cu) and a cubic law for thicker films (up to 1.5 µm). A number of works 228,274,282,283 find qualitative agreement with the Cabrera-Mott theory, however linear oxide growth has been observed in other studies 263,284,285 , as well as power (n < 1) 286 or parabolic law 287 .…”
Section: Long-term Copper Oxidationmentioning
confidence: 70%
“…growth of thickness of the oxide as a function of time, and they are summarised in Fig 11. A number of theories have been proposed [277][278][279][280] , mostly based on the Cabrera and Mott 281 theory and they postulate that, under the assumption of uniform epitaxial growth, the thickness of a metal oxide increases following an inverse logarithmic rate law for very thin films (up to 7.3 nm for Cu) and a cubic law for thicker films (up to 1.5 µm). A number of works 228,274,282,283 find qualitative agreement with the Cabrera-Mott theory, however linear oxide growth has been observed in other studies 263,284,285 , as well as power (n < 1) 286 or parabolic law 287 .…”
Section: Long-term Copper Oxidationmentioning
confidence: 70%
“…[10][11][12][13] Njeh et al 10 discuss the oxidation of copper thin films in air using x-ray reflectometry and x-ray diffraction at temperatures below 250 C. Ellipsometry, using 350 nm to 850 nm light, has also been employed successfully to characterize the oxidation kinetics by Iijima et al 11 It was shown by Zhong et al 12 that the measurement of the sheet resistance of copper layers during oxidation can also give information about the oxidation kinetics. In the latter technique, the change in sheet resistance was correlated with the thinning of the copper metal layer due to oxidation.…”
Section: Introductionmentioning
confidence: 99%
“…The formation of Cu 2 O was probably owing to the oxidation of a few layers of sintered copper during the heating process. 24) The results of the EDS analysis also suggested that a few sintered layers were in the form of a solid solution of the silver and copper nanoparticles (point 1 in Table 1), indicating that some of the copper nanoparticles were alloyed with the silver during the formation and sintering of the copper nanoparticles.…”
Section: Tensile Strength Of the Jointsmentioning
confidence: 97%